2015
DOI: 10.1021/acs.inorgchem.5b00369
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Properties of Red-Emitting Tris(cyclometalated) Iridium(III) Complexes Having Basic and Nitro Groups and Application to pH Sensing and Photoinduced Cell Death

Abstract: Cyclometalated iridium(III) complexes, because of their photophysical properties, have the potential for use as luminescent probes for cellular imaging. We previously reported on a pH-activatable iridium complex that contains three N,N-diethylamino groups, namely, fac-Ir(deatpy)3 5, which was synthesized via a regioselective aromatic substitution reaction at the 5'-position with tolylpyridine groups of fac-Ir(tpy)3 2. It was found that 5 shows a considerable enhancement in emission intensity in the pH range fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 128 publications
1
45
0
Order By: Relevance
“…Previously, we reported that the Ir complexes function as photosensitizers for the production of singlet oxygen ( 1 O 2 ) from triplet oxygen ( 3 O 2 ) to induce the death of HeLa cells, an adhesive cancer cell line . Thus, we checked the effect of the photoirradiation of the Ir complexes on the cell viability of Jurkat cells and found that Jurkat cells undergo cell death after photoirradiation ( λ = 465 nm) for 10 min even in the absence of the Ir complexes; therefore, the Jurkat cells are somewhat sensitive to photoirradiation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we reported that the Ir complexes function as photosensitizers for the production of singlet oxygen ( 1 O 2 ) from triplet oxygen ( 3 O 2 ) to induce the death of HeLa cells, an adhesive cancer cell line . Thus, we checked the effect of the photoirradiation of the Ir complexes on the cell viability of Jurkat cells and found that Jurkat cells undergo cell death after photoirradiation ( λ = 465 nm) for 10 min even in the absence of the Ir complexes; therefore, the Jurkat cells are somewhat sensitive to photoirradiation.…”
Section: Resultsmentioning
confidence: 99%
“…First, 2‐(4′‐methoxycarbonylphenyl)pyridine ( 8 ) was synthesized from 4‐(methoxycarbonyl)phenylboronic acid ( 6 ) and 2‐bromopyridine ( 7 ) in the presence of Pd(OAc) 2 and K 3 PO 4 in i PrOH/H 2 O (1:1) . The complexation of 8 with IrCl 3 was performed as described in our previous paper to give 9 , the methyl ester of which was hydrolyzed by treatment with aqueous NaOH and EtOH in freshly distilled tetrahydrofuran (THF) to obtain 10 . The condensation of 10 with mono‐Boc‐protected (Boc = tert ‐butyloxycarbonyl) diamine derivatives ( n = 2, 6, 8, 16) afforded 11 – 14 , and the subsequent removal of the Boc‐protecting group, gave 15 – 18 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional experiments were performed to determine the actual oxidant and formulate a plausible mechanism. In particular, the addition of NaN 3 ( 1 O 2 quencher, entry 4 in Table ) drastically suppressed the photooxidation of the substrate, and this suggested that the process is essentially mediated by 1 O 2 in an ET process . Other additives, such as 1,4‐benzoquinone (quencher of O 2 .− ) and 1,4‐dimethoxybenzene (scavenger of sulfide radical cations, R 2 S .+ ) (entries 5 and 6 in Table ) were also used as indirect probes for O 2 .− and R 2 S .+ .…”
Section: Resultsmentioning
confidence: 99%
“…In general, phosphorescent biscyclometalatedi ridium(III) complexes display very interesting emission properties, for example,h igh quantum yields, large Stokes shifts, long-lived phosphorescence, modular color-tuningp ossibilities, and good photostability.A saresult, they are being studied in the development of solid-state lighting devices,s uch as organic lightemitting diodes( OLEDs) [14] and light-emitting electrochemical cells (LECs), [15,16] as biological imaging agents, [17] and as analytical probes. [18] In addition, they work as efficient PSsi ns inglet oxygen production and can be used as O 2 probes, [19,20] as photodynamic anticancer agents, [21][22][23][24][25][26][27][28][29][30][31][32][33][34] and as catalysts in photooxidation reactions. [35] Previous reports have shown that biscyclometalated Ir III complexes with 2-(2-hydroxyphenyl)oxazolebased N^O ancillary ligands, similart ot hose used in this work, exhibit highly efficient phosphorescence.…”
Section: Introductionmentioning
confidence: 99%